Recent Progress in Flexible Pressure Sensors Based Electronic Skin - Pierre Claver, Uzabakiriho; Zhao, Gang (Advanced engineering materials, 2021)
In recent years, implantable electronics, electronic skin (e‐skin), and flexible wearable devices have been developed due to their extensive applications in health monitoring, intelligent robots, and human disease treatment. Tactile sensors are the keys necessary to build skin‐inspired electronics. This article reviews the latest progress of e‐skin‐based flexible pressure sensors, such as piezoresistivity, capacitance, triboelectricity, and piezoelectricity from 2018 up to now. The working principles, structure design, active materials, and performance of numerous flexible pressure sensors are covered in detail. Finally, insights are provided and challenges and future perspectives of flexible pressure sensors in practical applications are discussed. This article reviews the latest progress of electronic skin based flexible pressure sensors, such as piezoresistivity, capacitance, triboelectric, and piezoelectricity. The working principles, structure design, active materials, and performance of numerous flexible pressure sensors are covered in detail. Finally, insights are provided and challenges and future perspectives of flexible pressure sensors in practical applications are discussed.